Volcanic Fluxes Over the Last Millennium as Recorded in the Gv7 Ice Core (Northern Victoria Land, Antarctica) - Nardin, Raffaello; Amore, Alessandra; Becagli, Silvia; Caiazzo, Laura; Frezzotti, Massimo; Severi, Mirko; Stenni, Barbara; Traversi, Rita (Geosciences, 2020)
Major explosive volcanic eruptions may significantly alter the global atmosphere for about 2-3 years. During that period, volcanic products (mainly H2SO4) with high residence time, stored in the stratosphere or, for shorter times, in the troposphere are gradually deposited onto polar ice caps. Antarctic snow may thus record acidic signals providing a history of past volcanic events. The high resolution sulphate concentration profile along a 197 m long ice core drilled at GV7 (Northern Victoria land) was obtained by Ion Chromatography on around 3500 discrete samples. The relatively high accumulation rate (241 +/- 13 mm we yr (-1)) and the 5-cm sampling resolution allowed a preliminary counted age scale. The obtained stratigraphy covers roughly the last millennium and 24 major volcanic eruptions were identified, dated, and tentatively ascribed to a source volcano. The deposition flux of volcanic sulphate was calculated for each signature and the results were compared with data from other Antarctic ice cores at regional and continental scale. Our results show that the regional variability is of the same order of magnitude as the continental one.